2021
DOI: 10.1093/eurjpc/zwab192
|View full text |Cite
|
Sign up to set email alerts
|

Are polygenic risk scores for systolic blood pressure and LDL-cholesterol associated with treatment effectiveness, and clinical outcomes among those on treatment?

Abstract: Aims  Many studies have investigated associations between polygenic risk scores (PRS) and the incidence of cardiovascular disease (CVD); few have examined whether risk factor-related PRS predict CVD outcomes among adults treated with risk-modifying therapies. We assessed whether PRS for systolic blood pressure (PRSSBP) and for low-density lipoprotein cholesterol (PRSLDL-C) were associated with achieving SBP and LDL-C-related targets, and with major adverse cardiovascular events (MACE: non-fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Analyses of data from a randomized controlled trial (RCT) 10 found that age and baseline BP were associated with CCB response in ∼60 patients. Also, a UK Biobank study that included patients who reported antihypertensive use at baseline found SBP polygenic score was associated with uncontrolled BP (Odds ratio: 1.70; 95% CI: 1.6-1.8) 27 , top vs. bottom quintile. Another UK Biobank study testing cardiovascular associations with SBP polygenic score at baseline found high SBP increased the cardiovascular outcomes in untreated hypertension with 1.04-fold and in treated hypertension with 1.06-fold 44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyses of data from a randomized controlled trial (RCT) 10 found that age and baseline BP were associated with CCB response in ∼60 patients. Also, a UK Biobank study that included patients who reported antihypertensive use at baseline found SBP polygenic score was associated with uncontrolled BP (Odds ratio: 1.70; 95% CI: 1.6-1.8) 27 , top vs. bottom quintile. Another UK Biobank study testing cardiovascular associations with SBP polygenic score at baseline found high SBP increased the cardiovascular outcomes in untreated hypertension with 1.04-fold and in treated hypertension with 1.06-fold 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of data from a randomized controlled trial (RCT) 10 found that age and baseline BP were associated with CCB response in ~60 patients. Also, a UK Biobank study that included patients who reported antihypertensive use at baseline found SBP polygenic score was associated with uncontrolled BP (Odds ratio: 1.70; 95% CI: 1.6-1.8) 27 , top vs. bottom quintile.…”
Section: -Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that PRS add predictive value to current clinical risk algorithms and are largely independent of disease family history [6,7]. Systolic blood pressure (SBP) and LDL-cholesterol (LDL-C) are robustly predicted by the appropriate PRS developed in several studies including meta-analysis [8][9][10][11]. Risk algorithms are proposed to be useful for NCDs, and for diseases for which lifestyle or medical therapy to decrease causative risk is available [9].…”
mentioning
confidence: 99%
“…Systolic blood pressure (SBP) and LDL-cholesterol (LDL-C) are robustly predicted by the appropriate PRS developed in several studies including meta-analysis [8][9][10][11]. Risk algorithms are proposed to be useful for NCDs, and for diseases for which lifestyle or medical therapy to decrease causative risk is available [9]. Atherosclerotic cardiovascular diseases would fulfil both criteria, and including genetic information in risk models could potentially contribute to the improvement of personalized cardiovascular risk prediction or to the identification of high-risk patients, who might benefit from stricter treatment goals through treatments, as reported previously [12].…”
mentioning
confidence: 99%